(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research will discuss the reduction between Husserl and Merloponte, where reductionism is one of the elements of Husserl’s phenomenological approach, which is the way the transcendental ego is used to reach the anemones. Phenomenology has influenced many of the later philosophies, especially existentialism, where the latter attempted to apply Phenomenology from the arena of feeling to the realm of existence, and Merloponte as existential philosopher of the Phenomenology applied to his philosophy. This research will focus on how Husserl and Merloponte treated the reduction, and what are the points of intersection and difference between the philosophers. This research addresses the meaning of the Pythagorean and phoenomological and Mahawe reduction in each, and how Merloponte achieved a leap and overcome Husserl in a manner consistent with his philosophy based on perception.